Data from: Deconstructing an infamous extinction crisis: Survival of Partula species on Moorea and Tahiti - Haponski, Amanda; Lee, Taehwan; O' Foighil, Diarmaid (Dryad, 2019)
Eleven of eighteen Society Island Partula species endemic to the Windward
Island subgroup (Moorea and Tahiti) have been extirpated by an ill-advised
biological control program. The conservation status of this critically
endangered tree snail radiation is of considerable import, but is clouded
by taxonomic uncertainty due to the extensive lack of congruence among
species designations, diagnostic morphologies and molecular markers. Using
a combination of museum, captive, and remnant wild snails, we obtained the
first high-resolution nuclear genomic perspective of the evolutionary
relationships and survival of fourteen Windward Island Partula species,
totaling 93 specimens. We analyzed ~1,607-28,194 nuclear genomic loci
collected with the double digest Restriction-site Associated sequencing
method. Results from phylogenomic trees, species estimation, and
population assignment tests yielded monophyly of the Windward Island
subgroup. Within this group, two well-supported clades encompassing five
species complexes were recovered. Clade 1 was restricted to Tahiti and
contained two species complexes: “P. affinis” (three species) and “P.
otaheitana” (five species). Clade 2 occurred on Moorea and on Tahiti and
consisted of three species complexes: one Tahitian, “P. clara/P. hyalina”;
the other two, “P. taeniata” (three species) and “P. suturalis” (six
species), Moorean. Our genomic results largely corroborated previous
mitochondrial DNA survival estimates for Moorea and Tahiti, with all five
species complexes having members surviving in captivity and/or as remnant
wild populations, although the details vary in each case. Continued,
proactive conservation and management may yet ensure a
phylogenetically-representative survival of the fabled Partula species of
Moorea and Tahiti.
RAxML-matricesThe file contains the nine .phy formatted data matrices for
use in RAxML to construct the phylogenomic trees. The nine matrices were
generated using ipyrad. Files are named by the similarity threshold (85,
90, or 95%) and taxon coverage used (75, 50, or
25%).ipyrad-parameter-filesThe file contains the nine parameter files used
by ipyrad to generate all data matrices for downstream analyses. We used
three similarity threshold values (85, 90, and 95%) and three different
taxon coverages (75, 50, and 25% of individuals).mrbayes-data-matrixThis
file contains the data matrix from the 90% similarity threshold including
75% of individuals used for analysis in MrBayes. The nexus file was
generated by ipyrad.SI-AATTC-90-75.nex.gzSingle SNP VCF fileThis is the
single SNP file in vcf format that was used to generate inputs for
Structure, treemix, and DAPC analyses in the manuscript. File was created
using the python code vcf_single_snp.py (Bongaerts
2018).SI-90-75-sSNP-2169snp.vcfSVDquartets input fileThis is the file used
to generate the species estimation tree in
SVDquartetsSI-90-75-SVDquartets.nexTreemix inputThis is the input file
used to conduct the f3 admixture tests. The file contains seven
"populations" based on the structure
analyses.SI-90-75-sSNP-treemix.tmix.gzDAPC input filesThis file contains
all of the input files used for the DAPC analyses in the manuscript. They
are in genepop format and were generated from the single SNP vcf
file.DAPC-input.zipstructure-inputThis file contains all of the inputs
used for the five different structure analyses. The input files were
generated from the single SNP vcf and converted to the structure format
using PGDspider.
Keywords: Partula